Nitric Acid Extraction into the TODGA/TBP Solvent. Issue 4 (6th June 2016) - McLachlan, Fiona; Greenough, Katie; Geist, Andreas; McLuckie, Bliss; Modolo, Giuseppe; Wilden, Andreas; Taylor, Robin
ABSTRACT: The tridentate diglycolamide ligand N, N, N′, N′ -tetraoctyl diglycolamide (TODGA) shows many interesting properties and is a very good extractant for the minor actinides (MAs) and lanthanides but, due to its low loading capacity, requires a phase modifier when used in a solvent extraction process. Consequently, applications of TODGA in conjunction with tri-butyl phosphate (TBP) in novel DIAMEX and SANEX processes for recovering MAs have been reported. However, TODGA and TBP also extract nitric acid and this has a significant influence on process performance. Here new distribution data for the extraction of nitric acid into solvent phases containing TODGA and TBP have been collected and modeled using an equilibrium-based approach accounting for nitric acid activities in the aqueous phase. Models for the extraction of nitric acid using the individual extractants were obtained using a variety of complexes and these were then combined to give the extraction of the mixed TODGA and TBP solvent. Using this approach, the nitric acid extraction of the mixed TODGA/TBP system can be reliably reproduced indicating that no significant synergistic or antagonistic complexes are formed in solution.